1986
DOI: 10.1063/1.865673
|View full text |Cite
|
Sign up to set email alerts
|

Interchange, rotational, and ballooning stability of long-thin axisymmetric systems with finite-orbit effects

Abstract: The stability of axisymmetric tandem mirror plasmas with respect to interchange, rotational, and ballooning modes is investigated in the paraxial approximation. The stabilizing effects of finite orbits, rigid energetic fast-drifting electrons, nearby conducting walls, and line-tying by a cold plasma halo are incorporated. Numerical calculations are performed to construct equilibria with finite plasma pressure and to determine linear stability by integrating a two-dimensional, initial-value equation. These nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 39 publications
2
35
0
Order By: Relevance
“…4,5,8,9,11,12,14 The particle simulation has introduced no approximations in the basic laws of mechanics and electricity. So the FLR is expected to stabilize the interchange instability completely in the real magnetically confined plasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,8,9,11,12,14 The particle simulation has introduced no approximations in the basic laws of mechanics and electricity. So the FLR is expected to stabilize the interchange instability completely in the real magnetically confined plasma.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 The FLR effects on an interchange instability are also important in an open system such as a tandem mirror. [8][9][10][11][12] The generalized Ohm's law and gyroviscosity in the extended MHD equation were derived theoretically. 5,13 Recently, it has been reported that the complete FLR stabilization of the interchange mode may not be attainable by the gyroviscosity or generalized Ohm's law alone in the frame work of extended MHD.…”
Section: Introductionmentioning
confidence: 99%
“…and for the extra hot electrons in the end-cell core which are needed to stabilize the core, u> = (*/*_) (27) where ijj is the magnetic flux at the core plasma surface.…”
Section: Iii1 Hhd Equilibrium and Stabilitymentioning
confidence: 99%
“…1 was assessed by the FLORA MHD stability code 7 and with codes written using the Mathematica platform. The distance from the outer edge of the 0.42 m radius plasma to the flibe "wall" is taken to be 0.18 m and 0.75 m of flibe to the 30-mm thick steel wall followed by another 0.5 m of slowly flowing flibe.…”
Section: Configuration-equilibriamentioning
confidence: 99%